The Local Agrifood System Sustainability/Resilience Index (SRI): Constructing a data tool applied to counties in the southern United States. Issue 5 (20th October 2017) - Green, John J.; Worstell, Jim; Canarios, Caroline
Abstract: Discussions of sustainability, including local agrifood systems research, policy, and practice, increasingly address the concept of resilience. Indicators of resilience need further attention if they are to be useful for community development. This project involved conceptualization, operationalization, and measurement of indicators focused on the resilience of local agrifood systems to construct data-driven tools for theory building and informing development programs and policy, including at the local level. The Local Agrifood Systems Sustainability/Resilience Index was constructed through insights from literature and prior case studies. Building from that work emphasizing the importance of locally modifiable qualities of resilience, this study analyzes publicly available data sources at the county level. Piloted with data from counties in the southern US, findings suggest state and regional differences that may be informative to guide future explanatory research and for development and tracking change as new waves of data become available.